Revolusi Ekonomi Daulah Umayyah: Kebijakan Umar Bin Abdul Aziz dan Filosofi Kesejahteraan Islam - Nurhalisa; Tri Hidayati; Anas Wahid Maulana (PROGRAM STUDI EKONOMI ISLAM PROGRAM PASCASARJANA IAIN SULTAN MAULANA HASANUDDIN BANTEN, 2024)
This research discusses the economic revolution that occurred during the leadership of Umar bin Abdul Aziz in the Umayyad Daulah, with a focus on economic policies based on Islamic welfare principles. Umar bin Abdul Aziz is known as a leader who brought significant reforms in the economic system through various policies, such as equal distribution of zakat, elimination of unfair taxes, control of corruption, and redistribution of resources. These policies succeeded in creating social balance, reducing poverty levels, and improving relations between groups in society. Through a literature approach, this research analyzes how Umar bin Abdul Aziz's policies reflect the Islamic welfare philosophy which integrates material, social, moral and spiritual aspects. The research results show that Islamic economic principles, if applied consistently, are able to create sustainable justice and prosperity. In conclusion, Umar bin Abdul Aziz's economic policies provide a concrete example of how Islamic values ​​can be implemented in government to achieve broader social welfare.